2021
DOI: 10.1186/s13613-021-00929-y
|View full text |Cite
|
Sign up to set email alerts
|

Long-term survival of mechanically ventilated patients with severe COVID-19: an observational cohort study

Abstract: Background Information is lacking regarding long-term survival and predictive factors for mortality in patients with acute hypoxemic respiratory failure due to coronavirus disease 2019 (COVID-19) and undergoing invasive mechanical ventilation. We aimed to estimate 180-day mortality of patients with COVID-19 requiring invasive ventilation, and to develop a predictive model for long-term mortality. Methods Retrospective, multicentre, national cohort … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 47 publications
7
23
0
1
Order By: Relevance
“…Demographics, treatments and outcomes between patients described in this report and previous literature are similar, however major differences are the use of SDD and the incidence of VAP [ 1 3 ]. In support of our data, a recently published observational study, suggests a strong mortality benefit of SDD, although the incidence of VAP was not reported [ 6 ].…”
supporting
confidence: 89%
“…Demographics, treatments and outcomes between patients described in this report and previous literature are similar, however major differences are the use of SDD and the incidence of VAP [ 1 3 ]. In support of our data, a recently published observational study, suggests a strong mortality benefit of SDD, although the incidence of VAP was not reported [ 6 ].…”
supporting
confidence: 89%
“… 31 On the other hand, a Spanish study reported a better survival probability in mechanically ventilated COVID-19 patients (>50% after 180 days of follow up). 32 The meta-analysis of 69 studies by Lim et al reported a CFR of 45% (95% CI: 39 to 52%) among mechanically ventilated COVID-19. 33 The difference in CFRs reported in the literature might be related to quality of care, setting and/or regional differences.…”
Section: Discussionmentioning
confidence: 99%
“…This is line with previous reports that the severity of respiratory failure at admission is associated with disease progression and COVID-19-associated mortality [ 15 ]. Similarly, in a study of 868 patients receiving MV in the ICU for COVID-19, a failed attempt at non-invasive positive pressure ventilation prior to orotracheal intubation was associated with an almost 2-fold increase in 6-month mortality (odds ratio 1.878 (95% CI 1.124-3.140)) [ 16 ].…”
Section: Discussionmentioning
confidence: 99%